Necleoside conformations. 19. Temperature and pH effects on the conformation of guanosine phosphates. - Son, T D (1975)
Proton magnetic resonance spectra at 250 MHz were measured as a function of temperature and pH of the three guanosine phosphates. From these data and previously published work the conformational parameters of these compounds were determinated. The phosphate group of Guo-5'-P changes its conformation around the C-O bond and its rotation is relatively slow at 20 degrees. At neutral pD the S conformation is favoured and the N form at acid pD. This conformational change is paralleled by a change in exocyclic rotamer distribution and takes place at the pK of the protonation of the base on N-7. Although correlation appears to exist between the various conformations, notable exceptions exist.